Penerapan Program Ekstrakurikuler TdBA (Tatanen di Bale Atikan) dalam Membentuk Karakter Peserta Didik - Deti Yulianti; Divia Avivah; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
The Tatanen Program at Bale Atikan (TdBA) is an environment-based character education program developed to foster positive values ​​in students through agricultural activities at school. However, in its implementation, students are still found to have not consistently demonstrated a responsible attitude towards the tasks given and have not been optimal in working together during the activities. This study aims to find and analyze the implementation of the Tatanen Extracurricular program at Bale Atikan (TdBA) in improving student character. The approach used is a case study approach. Data collection methods were obtained through non-participatory observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that (1) The TdBA Program can improve responsible character through accustoming students to carrying out duty schedules, caring for plants, maintaining environmental cleanliness, and completing tasks without having to be constantly reminded; (2) The character of mutual cooperation develops through farming activities carried out in groups so that students are accustomed to working together, sharing tasks, helping each other, and appreciating the contribution of each group member. The conclusion of this study is that the Tatanen program at Bale Atikan has proven to be an effective environment-based character education strategy in improving students' responsible and cooperative character.